Optimizing fundamental design of soft magnetic layer to improve the energy conversion efficiency of airport pavement induction heating - Chen, Feng (2024)
A soft magnetic layer can improve the energy conversion efficiency via adjusting the magnetic field distribution during the airport pavement induction heating for ice and snow removal. In this work, electromagnetic simulations were performed to investigate the influence of key material parameters such as the magnetic permeability, thickness and position of soft magnetic layer on the magnetic field distribution in airport pavement during induction heating. The results show that a soft magnetic layer with a thickness of 1 cm can increase the induction heating efficiency of airport pavement by 58.88%, which shows great energy-saving potential. Artificial neural network (ANN) method was adopted to constructed the prediction model of the heat flux within heat generation layer considering the influence of magnetic permeability, thickness and position of soft magnetic layer and the external excitation, which provides application support for the soft magnetic layer design. In addition, mechanical simulations were conducted to analyze the influence of soft magnetic layer on the stress responses within airport pavement structure. It was found that provided the embedment depth of soft magnetic layer is no more than 8 cm, the critical pavement tensile stress can be controlled within 4.5 MPa that ensures the structural safety.